Every Business a Social Business: Fantasy or Destiny? - Tse, Ka Kui (Institutional Knowledge at Singapore Management University, 2012)
Business as usual is no longer enough, Ka Kui Tse insits. Corporations should be prepared to transition into social businesses or cease to be relevant.